Feeding ecology of electric eel Electrophorus varii (Gymnotiformes: Gymnotidae) in the Curiaú River Basin, Eastern Amazon - Mendes-Júnior,Raimundo Nonato Gomes (2020)
ABSTRACT In this study, the composition of the diet and the feeding activity of Electrophorus varii were evaluated. The influence of ontogeny and seasonality in these feeding parameters was also examined. Fish were collected in the Curiaú River Basin, Amazon, Brazil, from March 2005 to February 2006, during the rainy (January-June) and dry (July-December) seasons. Diet composition was characterized based on the analysis of stomach contents and feeding dynamics was assessed based on the Stomach Fullness Index (IR) calculated using stomach weight. Stomach content and RI data were grouped into four-cm size classes (40-80, 80-120, 120-160, and 160-200) and two seasonal periods (rainy and dry). The influence of ontogeny and seasonality in the diet was investigated through PERMANOVA, and in the food dynamics through ANOVA. The analysis of stomach contents revealed that fish were the most consumed preys by electric eels, especially Callichthyidae and Cichlidae. Diet composition and RI values of electric eels were not influenced by ontogeny and seasonality. Electric eels are fish predators, regardless of size class and seasonal period.